Capital structure of listed property firms: Lessons from a property investment reform - Francois Toerien; Alessandro Calvosa; Phillip G. de Jager (South African Journal of Economic and Management Sciences)
Background: In 2013, most South African listed properties converted from legal structures allowing unlimited leverage and tax-deductible interest to real estate investment trusts (REITs), which limit leverage and eliminate interest tax-shield benefits.